2012
DOI: 10.1093/ntr/nts205
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Carbon Monoxide Criteria to Confirm 24-hr Smoking Abstinence

Abstract: introduction:Smoking cessation is typically verified biochemically by expired-air carbon monoxide (CO) levels below 9 ppm (i.e., ≤8 ppm), but this CO criterion may lead many who have smoked within 24 hr to be misclassified as abstinent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
114
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(123 citation statements)
references
References 21 publications
8
114
0
1
Order By: Relevance
“…19,20 At week 26, 7-day point prevalence abstinence rate was determined as a participant report of more than 7 days of continuous abstinence from any tobacco use and an exhaled CO level less than or equal to 3 parts per million. These criteria are similar to recent recommendations for documenting smoking abstinence 65,66 and are comparable to criteria used in other treatment studies. [67][68][69] Participants who initiated treatment, but dropped out of the study, were classified as non-abstinent, in accordance with recent recommendations 65,70 and use of this classification in smoking cessation treatment research.…”
Section: Study Treatmentssupporting
confidence: 59%
“…19,20 At week 26, 7-day point prevalence abstinence rate was determined as a participant report of more than 7 days of continuous abstinence from any tobacco use and an exhaled CO level less than or equal to 3 parts per million. These criteria are similar to recent recommendations for documenting smoking abstinence 65,66 and are comparable to criteria used in other treatment studies. [67][68][69] Participants who initiated treatment, but dropped out of the study, were classified as non-abstinent, in accordance with recent recommendations 65,70 and use of this classification in smoking cessation treatment research.…”
Section: Study Treatmentssupporting
confidence: 59%
“…With an urban sample, many of whom were unhoused, we used a CO cutpoint of 10 parts per million for abstinence, which may be less than optimal for light smokers. 61 Nevertheless, the promising findings from this study warrant a larger trial among low-income, diverse smokers with serious mental illness with assessment of costs to deliver the intervention and return on investment. Notably, in the parent trial, the intervention, evaluated in inpatient psychiatry, was found to be highly cost-effective with an incremental cost-effectiveness ratio of $428 per quality adjusted life year.…”
Section: Discussionmentioning
confidence: 88%
“…Recruitment consisted of presentations at OB/GYN clinics, flyers and advertising on social media. Eligibility included: women 18-35 years old; stable physical/mental health; uncomplicated, single gestational pregnancy with established prenatal care; a signed letter from their OB physician confirming no pregnancy-related complications (ie, gestational diabetes, fetal growth restriction, pregnancy hypertension, history of ≥3 miscarriages, known congenital anomaly); self-report of no smoking for 4 weeks prior to study enrollment (at 32-35 weeks gestation), confirmed with carbon monoxide (CO) < 5 ppm 23 ; previous history of five cigarettes per day (CPD) for at least 6 of the past 12 months; motivated to remain abstinent after delivery (≥7 on 10-point Likerttype scale); willing to use nonhormonal birth control during the postpartum follow-up period of the study; English fluency; and ability to provide informed consent. Ineligibility items included: self-reported use of illicit drugs, nicotine replacement therapy, smoking cessation medications, or medications contraindicated to progesterone use (ie, drugs that may inhibit CYP3A4 functioning); contraindications to progesterone treatment (ie, history of thrombophlebitis, deep vein thrombosis, pulmonary embolus, clotting/bleeding disorders, stroke, heart disease, diabetes, liver dysfunction or disease, or an allergy to peanuts (progesterone capsules contain peanut oil).…”
Section: Participantsmentioning
confidence: 99%
“…Smoking status or abstinence was confirmed by breath CO measurements (CO < 5 ppm indicating abstinence) 23 serum cotinine (<4.47 ng/ml indicating abstinence) 41 analysis and self-report via the Timeline Followback procedure 33,34 at each clinic visit. Cotinine levels for weeks 0, 4, and 12 were analyzed.…”
Section: Smoking Statusmentioning
confidence: 99%